2021
DOI: 10.1108/ecam-07-2021-0632
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the schedule performance resulting from the adoption of social distancing in construction projects

Abstract: PurposeThe coronavirus disease 2019 (COVID-19) pandemic has had major impacts on the performance of construction projects that have adopted social distancing measures. This study examines the effect of social distancing measures on project schedule performance through job reorganization on construction project sites.Design/methodology/approachResponses were obtained through a survey of 154 construction projects and analysed using the partial least square structural equation modeling (PLS-SEM) technique.Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Evans et al (2021) examined several job outcomes caused by the transition to remote work enforced by the pandemic and found a significant decline in the performance of self-reporting employees. Similar results were also reported by Onubi et al, 2021, who observed a major negative impact of social distancing measures enforced during COVID-19 on the performance of construction projects. These conflicting results call for more detailed examinations of the impact of the COVID-19 outbreak on employees' job performance.…”
Section: Literature Reviewsupporting
confidence: 89%
“…Evans et al (2021) examined several job outcomes caused by the transition to remote work enforced by the pandemic and found a significant decline in the performance of self-reporting employees. Similar results were also reported by Onubi et al, 2021, who observed a major negative impact of social distancing measures enforced during COVID-19 on the performance of construction projects. These conflicting results call for more detailed examinations of the impact of the COVID-19 outbreak on employees' job performance.…”
Section: Literature Reviewsupporting
confidence: 89%
“…In 2021, with the strong call from the central government, governments at all levels attached great importance to urban regeneration initiatives and introduced a series of implementation plans that have achieved good results and more positive public comments. Whereas, by 2022, there were more negative comments about urban regeneration due to the increase in management repair issues across numerous post-implementation urban regeneration projects, as well as the delays or even suspension of projects due to the recurrence of the SARS-CoV-2 epidemic [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Also, in order to ensure compliance with the safety protocols associated with COVID-19 prevention, new roles need to be created and competencies need to be developed to check and guarantee compliance (Rydenf€ alt et al, 2014). The new roles and competencies could be in the aspect of carrying out prework tests such as temperature checks, questions at security and training on how to identify the symptoms of infection with COVID-19 (Mitra et al, 2020;Onubi et al, 2021b). This will require extra resources in terms of manpower and money from the contract sum, thus adversely affecting the EP of the project.…”
Section: Specific Training and Economic Performancementioning
confidence: 99%
“…The new roles and competencies could be in the aspect of carrying out prework tests such as temperature checks, questions at security and training on how to identify the symptoms of infection with COVID-19 (Mitra et al. , 2020; Onubi et al. , 2021b).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%